116. Functional connectivity between cortical speech network and primary motor cortex is abnormal in spasmodic dysphonia. Issue 1 (January 2015) - Giovannelli, F.; Marsili, L.; Suppa, A.; Di Stasio, F.; Rocchi, L.; Upadhyay, N.; Cincotta, M.; Ruoppolo, G.; Berardelli, A.
<x xml:space="preserve">Abstract</x> In healthy humans, the execution of linguistic tasks modifies the excitability of the hand area of the dominant primary motor cortex (M1), as tested by TMS. Our aim was to investigate the effect of linguistic tasks on the excitability of the M1 in patients with adductor type-spasmodic dysphonia (ASD), before and after Botulinum Neurotoxin Type A (BoNT-A) injections. We studied 10 patients with ASD and 10 age-matched healthy subjects. All participants were right handed. The excitability of either M1 hand area was evaluated at the baseline and during different linguistic and non-linguistic tasks: (1) reading aloud of single words; (2) silent reading; (3) looking at meaningless non-letter strings; (4) oral movements without vocalization; (5) producing simple syllabic phonation. In healthy controls, the motor evoked potential (MEP) elicited by TMS of the dominant M1 were significantly larger during reading aloud. In ASD patients, MEP enhancement in the dominant hand emerged not only during reading aloud but also during syllabic phonation. BoNT-A injections restored the neurophysiologic abnormalities. We conclude that ASD is characterized by an abnormal excitability of the hand area of the dominant M1 during specific linguistic tasks. This likely reflects an altered functional connectivity between cortical speech network and M1.